Analyze The Effect Of Internal Marketing Environment Variables On Bank Profitability An Applied Study On The Private Banking Sector In Syria During The Crisis Period (2011-2017) - بوحسون, ياسر; شعبان, هبة (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aims to clarify the effect of internal marketing environment variables on the profit of private banks in Syria during the period 2011-2017, where the relationship between profitability measured by the rate of return to assets as a dependent variable has been studied, and the following independent variables that represent the elements of the internal marketing environment: financial resources, resources Moral, material resources, human resources and administrative organization, and by relying on the program (E-views) to test the research hypotheses and verify their validity and link between independent variables and the dependent variable through the use of a cross-sectional data analysis method (Panel data) for the research sample, which included five of Private Syrian banks, and the study found that there is a statistically significant relationship between the variables of the internal marketing environment (financial resources, administrative organization and organizational structure) and the profitability of banks measured by the rate of return to assets.